2018
DOI: 10.1016/j.jgeb.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Production of biomass and flavonoid of Gynura procumbens (Lour.) Merr shoots culture in temporary immersion system

Abstract: Gynura procumbens (Lour.) Merris one of medicinal plant which was carried out used as antioxidant, anticancer, anti-inflammatory, hepatoprotective, and antimicrobial. Many strategies were used to increase the production of biomass and valuable compounds. This study was to investigate the variation effect of growth regulators and immersion frequency on production of biomass and flavonoid contained of G. procumbens shoots culture in temporary immersion bioreactor. Stem nodes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…2020) who achieve increased shoot length, roots, number of leaves and dry weight with prolonged frequency (8 h), when compared to a short frequency (4 h) in myrtle (M. communis). However, these frequencies are not always optimal to achieve a higher number of shoots and roots per explant (Arano et al 2020;Pramita et al 2018), concomitant with what was reported in our study. A possible explanation for the increase in shoot and root length with prolonged frequencies is that plants respond to water stress with the synthesis of abscisic acid, which is synthesized mainly in roots and leaves (Parkash y Singh, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…2020) who achieve increased shoot length, roots, number of leaves and dry weight with prolonged frequency (8 h), when compared to a short frequency (4 h) in myrtle (M. communis). However, these frequencies are not always optimal to achieve a higher number of shoots and roots per explant (Arano et al 2020;Pramita et al 2018), concomitant with what was reported in our study. A possible explanation for the increase in shoot and root length with prolonged frequencies is that plants respond to water stress with the synthesis of abscisic acid, which is synthesized mainly in roots and leaves (Parkash y Singh, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…Castilleja tenuiflora shoots from an immersion cycle of 30 min every 24 h showed the highest total phenolics (30.58 mg GAE/g DW) and total flavonoid content (45.83 µg CE/g DW) [118], while a lower immersion frequency of 15 min every 12 h increased only the flavonoid (32.00 mg catechin equivalent-CE/g DW) in shoot culture of Gynura procumbens [125]. In Rosa canina plantlets, two immersions per day (15 min/12 h) led to larger content of phenolic compounds (15.8 mg/g FW), whereas more immersions (15 min/6 h) produced a higher accumulation of soluble sugars (9.2 mg/g FW; [132]).…”
Section: Immersion Frequency and Bioactive Compounds Contentmentioning
confidence: 96%
“…Additionally, BA was observed to increase the growth of shoots in Gynura procumbens (Lour.) Merr, which is a medicinal plant that has antioxidant, anticancer, anti-inflammatory, hepatoprotective, and antimicrobial activities [ 74 ]. Furthermore, BA was found to improve the antioxidant enzyme activities and total antioxidant capacity and maintain higher levels of ATP content and energy charge in plants [ 75 ].…”
Section: Cytokinin Action In Plantsmentioning
confidence: 99%